Molecular Breeding of Forage and Turf - Yamada, Toshihiko; Spangenberg, German; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
This book includes papers from plenary lectures and selected oral presentations of the 5th International Symposium on the Molecular Breeding of Forage and Turf. A wide variety of themes are addressed in a collection that provides authoritative reports on the recent progress and understanding of molecular technologies and their application in plant breeding. The book covers almost all relevant areas in molecular breeding of forage and turf as well as biofuel crops, from gene discovery to the development of improved cultivars. The Symposium includes keynote presentations from international science leaders in molecular breeding of forage and turf and offers papers in the following topics: Molecular breeding to improve forages for use in animal and biofuel production systems DREB regulons in abiotic-stress-responsive gene expression in plants Comparative genomics in legumes Characterization and utilization of genetic resources Functional genomics of forage and bioenergy quality traits in the grasses Genome mapping in cool-season forage grasses Improving selection in forage, turf, and biomass crops using molecular markers Fungal endophytes in Lolium and Festuca species Colonial bentgrass genetic linkage mapping Advances and prospects in the molecular breeding of Zoysia Transgenesis in forage crops The 5th International Symposium on the Molecular Breeding of Forage and Turf is a valuable resource for plant breeders, geneticists and molecular biologists, and will be an interest to advanced undergraduates, postgraduates and researchers with an interest in forage and turf improvement. Dr. Toshihiko Yamada is a professor of Field Center for Northern Biosphere, Hokkaido University, Japan. Dr. German Spangenberg is Executive Director of Biosciences Research Division, Department of Primary Industries, Victorian AgriBiosciences Centre, Australia.
Molecular Breeding to Improve Forages for Use in Animal and Biofuel Production Systems -- DREB Regulons in Abiotic-Stress-Responsive Gene Expression in Plants -- Comparative Genomics in Legumes -- Development of Trifolium occidentale as a Plant Model System for Perennial Clonal Species -- Characterization and Utilization of Genetic Resources for Improvement and Management of Grassland Species -- Genomic and Geographic Origins of Timothy (Phleum sp.) Based on ITS and Chloroplast Sequences -- Diploid Brachypodium distachyon of Turkey: Molecular and Morphologic Analysis -- Remnant Oak Savanna Acts as Refugium for Meadow Fescue Introduced During Nineteenth Century Human Migrations in the USA -- Development of Microsatellite Markers for Brachiaria brizantha and Germplasm Diversity Characterization of this Tropical Forage Grass -- Functional Genomics of Forage and Bioenergy Quality Traits in the Grasses -- Proanthocyanidin Biosynthesis in Forage Legumes with Especial Reference to the Regulatory Role of R2R3MYB Transcription Factors and Their Analysis in Lotus japonicus -- Molecular Dissection of Proanthocyanidin and Anthocyanin Bosynthesis in White Clover (Trifolium repens) -- Transcript Profiling of Cold Responsive Genes in Medicago falcata -- Genetic Diversity and Association Mapping of Three O-Methyltransferase Genes in Maize and Tropical Grasses -- QTL Analysis and Gene Expression Studies in White Clover -- Genome Mapping in Cool-Season Forage Grasses -- Understanding the Genetic Basis of Flowering and Fertility in the Ryegrasses (Lolium spp.) -- Improving Selection in Forage, Turf, and Biomass Crops Using Molecular Markers -- Interpretation of SNP Haplotype Complexity in White Clover (Trifolium repens L.), an Outbreeding Allotetraploid Species -- Development of Marker-Assisted Selection for the Improvement of Freezing Tolerance in Alfalfa -- Comparative Analysis of Disease Resistance Between Ryegrass and Cereal Crops -- White Clover Seed Yield: A Case Study in Marker-Assisted Selection -- Molecular Mapping of QTLs Associated with Important Forage Traits in Tall Fescue -- Utilizing Linkage Disequilibrium and Association Mapping to Implement Candidate Gene Based Markers in Perennial Ryegrass Breeding -- Genetic Diversity in Australasian Populations of the Crown Rust Pathogen of Ryegrasses (Puccinia coronata f.sp. lolii) -- Fungal Endophytes in Lolium and Festuca Species -- Seed Transmission of Endophytic Fungus, Neotyphodium occultans, in Cross Breeding of Italian Ryegrass (Lolium multiflorum) Using Detached Panicle Culture, and Comparison with Situations in Interspecific/Intergeneric crossings including Festuca species -- Colonial Bentgrass Genetic Linkage Mapping -- Advances and Prospects in the Molecular Breeding of Zoysia -- Transgenesis in Forage Crops -- Evaluating the Role of Habitat Quality on Establishment of GM Agrostis stolonifera Plants in Non-agronomic Settings.
Keywords: LIFE SCIENCES; FORESTS AND FORESTRY; BOTANY; PLANT BREEDING; PLANT PHYSIOLOGY; LIFE SCIENCES; PLANT SCIENCES; PLANT GENETICS & GENOMICS; PLANT PHYSIOLOGY; FORESTRY